2009
DOI: 10.1007/s11605-008-0751-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Characteristics of Hepatocellular Carcinoma with Bile Duct Invasion

Abstract: To clarify the characteristics of hepatocellular carcinoma (HCC) with bile duct invasion, we retrospectively analyzed clinical features and surgical outcome of HCC with bile duct invasion (b(+) group, n = 15) compared to those without bile duct invasion (b(-) group, n = 256). In the b(+) group, four patients (27%) showed obstructive jaundice, and a diagnosis of bile duct invasion was obtained preoperatively in seven patients (47%). The levels of serum bilirubin and carbohydrate antigen 19-9 were significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
95
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(107 citation statements)
references
References 15 publications
6
95
6
Order By: Relevance
“…Early recurrence has been associated with poor prognosis (20) . Ikenga et al (17) , Qin et al (7) , Noda et al (21) , Shao et al (22) and Zeng et al (18) -all these studies reported > 50 % recurrence in less than one year. In our study we observed early recurrence in 20 cases.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Early recurrence has been associated with poor prognosis (20) . Ikenga et al (17) , Qin et al (7) , Noda et al (21) , Shao et al (22) and Zeng et al (18) -all these studies reported > 50 % recurrence in less than one year. In our study we observed early recurrence in 20 cases.…”
Section: Resultsmentioning
confidence: 95%
“…Recurrences were noted even in cases without vascular invasion. Shao et al (22) and Ikenaga et al (17) demonstrated tumor recurrences in cases without evidence of major vascular invasion. This indicates that dissemination via bile duct route could be another possible cause for recurrence.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Tumor thrombus in the bile duct in HCC is rare (0.79-5.5%) and the most common clinical manifestations are obstructive jaundice, abdominal pain, recurrent cholangitis or hemobilia. Biliary thrombi may be secondary to invasion of a primary liver tumor or due to a primary HCC arising on ectopic liver tissue located in the bile duct (2).…”
Section: Dear Editormentioning
confidence: 99%
“…HCC may manifest a variety of gross morphologies, including nodular, nodular with perinodular extension, multinodular confluent, and infiltrative types (15); each morphology is associated with different degrees of malignancy and variable clinical outcomes (16)(17)(18). While some HCC shapes, such as focal nodular varieties, have been associated with more favorable prognoses (19), other HCC morphologies, such as infiltrative and multinodular confluent forms, have been linked to poor patient survival (20,21). Current HCC morphologic imaging assessment is limited to subjective and qualitative descriptions, which may be confounded by inter-observer variation and lack the measurable parameters that allow reproducible tumor morphologic descriptions, numerical comparisons of tumor shapes, and the association of tumor contour descriptors with clinical outcomes.…”
mentioning
confidence: 99%